Controversies in the treatment of Lung cancer: 12th International Symposium on Special Aspects of Radiotherapy, Berlin, October 2008 - Heide, Jürgen (Frontiers of radiation therapy and oncology, 2010)
Under the auspices of the 12th International Symposium on Special Aspects in Radiotherapy 2008 in Berlin, acknowledged experts presented their perspectives on small and non-small cell lung cancer, reflecting the latest standards and engaging in controversies in the diagnosis and treatment of this disease.In the first part of this volume, aspects of the diagnostic workup are highlighted from the histopathologist’s point of view, followed by presentations concerning the value of PET-CT and whole-body MRI in the staging of lung cancer. The use and current methods in bronchoscopy, endoscopic ultrasound, video-endoscopy and mediastinoscopy are discussed in detail. The second section presents surgical and radio-oncological treatment concepts for stage I/II non-small cell lung cancer including stereotactic radiotherapy. The third section outlines the curative options for stage III NSCLC: extended surgical approaches , definitive radiochemotherapy and current concepts in adjuvant therapies. Emphasis is also placed on altered fractionation schemes in radiotherapy. Section 4 is dedicated to palliative procedures and the last section gives an in-depth presentation of small cell lung cancer.This book provides an excellent overview of up-to-date standards and future strategies in lung cancer treatment. It will be of great value to surgeons, radiation oncologists, pulmonary specialists and other clinicians interested in this disease
Latest diagnosis and treatment of small and non-small cell lung cancer
Keywords: Konferenzschrift -- 2008 -- Berlin